An analysis of the implementation of business process re-engineering in public services - Vishakha Wijeratne Elapatha; Shahzdah Nayyar Jehan (Journal of Open Innovation: Technology, Market, and Complexity, 2020)
Sri Lankan public service apparatus has a long colonial heritage, and all of that has not been in line with the requirements of a 21st century public service expectations. However, the increasing societal pressure for the delivery of more modern public services has forced it to undergo a major overhaul of its business process. In this paper, we assess the impact of the recent efforts at business process reengineering (BPR) in public service. We estimate the overall as well as relative efficiency of public service delivery across various ministries and departments of the Sri Lankan government. A broad-based Likert scale field survey on a five-point scale was carried out and performance data were collected. We applied a non-parametric data envelopment analysis (DEA) to estimate the overall and relative efficiency of the public service delivery across 29 departments and ministries (D&Ms) and the departments of the government of Sri Lanka. Our results show that, save for a few, most D&Ms have a potential for improving the performance. The performance enhancement is desirable both from an input as well as output perspectives. Moreover, our results indicate significant scale inefficiencies associated with the performance of ministries and departments that are engaged in public service delivery (PSD) in the country. The authors have also indicated towards critical success factors for a wider deployment of the study's findings in the conclusion.
Keywords: 650; BPR; DEA; public service delivery; open innovation; Sri Lanka